Energy and coincidence time resolution measurements of CdTe detectors for PET - Ariño, G. (2013)
We report on the characterization of 2 mm thick CdTe diode detector with Schottky contacts to be employed in a novel conceptual design of PET scanner. Results at −8°C with an applied bias voltage of −1000 V/mm show a 1.2% FWHM energy resolution at 511 keV. Coincidence time resolution has been measured by triggering on the preamplifier output signal to improve the timing resolution of the detector. Results at the same bias and temperature conditions show a FWHM of 6 ns with a minimum acceptance energy of 500 keV. These results show that pixelated CdTe Schottky diode is an excellent candidate for the development of next generation nuclear medical imaging devices such as PET, Compton gamma cameras, and especially PET-MRI hybrid systems when used in a magnetic field immune configuration.